SAFETY OF HUMAN ACTIVITY - DETECTION AND ASSESSMENT OF THE CHEMICAL SITUATION AFTER AN ACCIDENT AT A FACILITY WITH A SPILL OF NPH - Кудрявицька, Аліна (Modern engineering and innovative technologies, 2022)
Abstract. Chemical protection of the population includes measures to identify and assess the chemical situation, the organization and implementation of chemical control, providing the population with means of individual and collective protection, the orga